O centro de controle de zoonoses de mossoró rio grande o norte e sua relação com o bem estar animal e a comunidade - Costa, Vilcelânia Alves (Universidade Federal Rural do Semi-Árido, 2015)
The issues related to animal welfare (BEA) and bioethics has been the subject of much debate, especially when referring to the Zoonosis Control Centers (CCZ). That body is responsible for controlling the population of animals and, consequently, existing zoonoses in cities. In this context, can be seen problems due to a variety of factors that often affect not only public health but also animal welfare and the possibility of conflict between professionals of the institution and the population they served. Whereas, therefore, such a reality, aimed to analyze the CCZ serving Mossoró / RN, its relationship with the community and animal welfare. For this, we conducted field research on site CCZ, with observation and monitoring of the activities developed by the institution, as well as a questionnaire with open and closed questions to 36 employees of the CCZ. The research is still extended to five districts of the city, where questionnaires were applied, also with open and closed questions, the 385 residents of their neighborhoods. The data obtained after the questionnaires were subjected to statistical analysis using the R program, using the chi-square test, Fisher exact test, with a 5% significance level. From the observation of the activities developed by the local CCZ was found that this does not meet all the specific objectives set by the National Health Foundation (FUNASA), and its physical structure is not consistent with the proposed guidelines also for this, which compromises the welfare of the animals housed. Furthermore, although most professionals (78%) know what is animal welfare, only a small portion (28%) know issues related to bioethics, and 30% of those who know what bioethics has completed higher education, 10% have incomplete higher education, 50% have completed secondary level and 10% have completed secondary level. Regarding the perception of the community, the majority of respondents do not know what are the animal disease control centers, their purpose and which existing programs. Regarding the perception of the CCZ professionals about their relationship with the community conflicting data were highlighted, since they consider that their relationship is harmonious, but report that there is resistance from the population for their work. It follows that there is a perceived need on the expansion of services offered by the CCZ to the population in order to enable it to participate and collaborate in the control of zoonoses and control of stray animals. In addition, it is necessary to improve with regard to working conditions in the institution in order to ensure animal welfare and staff. However, this will only become feasible with efforts and interest of the government
The center mossoró rio grande zoonoses control the north and Its relationship with animal welfare and the community
Keywords: Zoonoses; Public health service; Bioethics; Zoonoses; Serviço público de saúde; Bioética; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE